Przedstaw podane wyrażenie jako jeden logarytm.

a)
[tex] log \frac{1}{2} 10 - 1[/tex]
b)
[tex]4 - log3[/tex]
c)
[tex]1 - log5[/tex]



Odpowiedź :

[tex]\log_{\frac{1}{2}}10-1=\log_{\frac{1}{2}}10-\log_{\frac{1}{2}}\frac{1}{2}=\log_{\frac{1}{2}}\left(10:\frac{1}{2}\right)=\log_{\frac{1}{2}}20 \\ \\ 4-\log3=\log10000-\log3=\log\frac{10000}{3} \\ \\ 1-\log5=\log10-\log5=\log2[/tex]

Skorzystałam z definicji logarytmu: [tex]\log_ab=c \ \Longleftrightarrow \ \ a^c=b[/tex]

oraz własności [tex]\log_ax-\log_ay=\log_a(x:y)[/tex]